2009
DOI: 10.1111/j.1747-9991.2009.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetics and Cognitive Science

Abstract: Experiences of art involve exercise of ordinary cognitive and perceptual capacities but in unique ways. These two features of experiences of art imply the mutual importance of aesthetics and cognitive science. Cognitive science provides empirical and theoretical analysis of the relevant cognitive capacities. Aesthetics thus does well to incorporate cognitive scientific research. Aesthetics also offers philosophical analysis of the uniqueness of the experience of art. Thus, cognitive science does well to incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…This is all the more surprising because there are obvious natural connections between aesthetics and cognitive sciences: aesthetics is not only interested in aesthetic properties, be they instantiated in natural objects or works of art, but also in aesthetic experience and the psychological mechanisms underlying the appreciation of said aesthetic properties (Stokes, ). For example, imagination is a topic that has attracted the attention both of cognitive scientists and aestheticians, fostering exciting interdisciplinary dialogues (see, for example, Paul Harris' work on imagination in Harris, , but also the discussion of imagine resistance by Weinberg & Meskin , , grounded on the account of imagination developed by Nichols and Stich, ).…”
Section: Neuroaesthetics Empirically Informed Aesthetics and Experimentioning
confidence: 99%
“…This is all the more surprising because there are obvious natural connections between aesthetics and cognitive sciences: aesthetics is not only interested in aesthetic properties, be they instantiated in natural objects or works of art, but also in aesthetic experience and the psychological mechanisms underlying the appreciation of said aesthetic properties (Stokes, ). For example, imagination is a topic that has attracted the attention both of cognitive scientists and aestheticians, fostering exciting interdisciplinary dialogues (see, for example, Paul Harris' work on imagination in Harris, , but also the discussion of imagine resistance by Weinberg & Meskin , , grounded on the account of imagination developed by Nichols and Stich, ).…”
Section: Neuroaesthetics Empirically Informed Aesthetics and Experimentioning
confidence: 99%
“…135 For more work at the intersection of philosophical aesthetics and cognitive science, see Shimamura and Palmer, 136 Goldie and Schellekens, 137 Currie et al, 138 and Currie et al 139 For another overview of cognitive science and aesthetics, see Stokes. 140 The preceding has shown that the relationship between contemporary aesthetics and cognitive science is a fruitful one. Not only are aestheticians taking on board the results of the cognitive sciences, they are making substantive contributions to the cognitive science themselves-both by cataloging intriguing aesthetic phenomena and by doing their own experimental research.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the significance of findings about mirror neurons for the philosophy of dance has been hotly debated, and there is a growing body of work at the intersection of the philosophy of music and cognitive science on such topics as musical understanding and musical emotions . For more work at the intersection of philosophical aesthetics and cognitive science, see Shimamura and Palmer, Goldie and Schellekens, Currie et al, and Currie et al For another overview of cognitive science and aesthetics, see Stokes …”
Section: Discussionmentioning
confidence: 99%
“…The psychology of aesthetic experience is focused on the mental processes that are related to the sensory valuation across various forms of art such as visual art, architecture, dance and music (Skov & Nadal, 2018, 2019 as well as non-art contexts, such as facial attractiveness or natural scenes (Aharon et al, 2001;Augustin et al, 2012;Fischer et al, 2018;Hagerhall et al, 2004;Han, 2007;Martín-Loeches et al, 2014;Vartanian et al, 2019;Vessel et al, 2018). In contrast, the psychology of art is a branch of aesthetics that is concerned more specifically with aesthetic experiences that are tied to art contexts (Goldman, 2001;Nadal & Skov, 2015;Stokes, 2009). Although art experience is just one type of aesthetic experience, the terms 'art' and 'aesthetics' are often used interchangeably.…”
Section: Introductionmentioning
confidence: 99%